The Roles of Attitudinal Perceptions and Cognitive Achievements in a Serious Game. (March 2015) - Cheon, Jongpil; Chung, Sungwon; Lee, Sangno
This study investigated a conceptual model that connects game expertise, attitudinal perceptions, and cognitive achievements, and behavioral intention in digital game-based learning. In the study, attitudinal perceptions consisted of three constructs: perceived enjoyment, perceived usefulness, and satisfaction, and cognitive achievements consisted of two constructs: game scores and recall of content. A total of 298 college students played a serious game about transistor recycling, and structural equation modeling was used to analyze data. Our findings showed that two attitudinal constructs (i.e., perceived enjoyment and perceived usefulness) and one cognitive achievement (i.e., game scores) positively influenced satisfaction, and then their satisfaction positively influenced both their recall of content and behavioral intention while game expertise significantly affected on perceived usefulness. This complementary relationship between attitudinal perceptions and cognitive achievements found in this study suggests that when designing a serious game, game designers need to consider the interplay between entertaining factors and instructional strategies.